Near Critical and Supercritical Fluid Extraction of Cu(Ii) from Aqueous Solutions Using a Hollow Fiber Contactor - Romero-Figueroa, J (2013)
The aim of this work is the experimental and theoretical characterization of the mass transfer in a membrane-based dense gas extraction of metal ions from aqueous solutions using a hollow fiber contactor. Extractions of Cu(II) were conducted in a single fiber membrane contactor operating under steady state conditions. Aqueous CuSO4 solutions were treated using a CO2 phase containing 1,1,1-trifluoro-2,4-pentanedione (TFA) or 1,1,1,5,5,5-hexafluoro-2,4-pentanedione (HFA) at 40°C and pressures ranged between 70 and 90bar.Experiments show that the use of dense CO2 as extraction solvent of Cu(II) ions reaches extraction efficiencies valued up to 98.7%. Simultaneously, a mass transfer model was proposed correlating an effective rate function of the complex formation at the aqueous-CO2 interface.The highest extraction efficiencies were observed at higher pressures and lower pH values, which could confirm that a high content of protons is required to facilitate and stabilize the formation complex by means of keto-enol tautomerism.This work represents the first step in order to propose a novel intensified operation, which could be applied for high valued metals or hazardous materials. © 2012 Elsevier B.V.